2013
DOI: 10.5005/johcd-7-1-24
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health Status and Treatment Needs of Inmates in District Jail of Mathura City – A Cross Sectional Study

Abstract: OBJECTIVES: To assess the oral health status and treatment needs of inmates of, District Jail Mathura. MATERIALS AND METHODS: A cross sectional study was carried out on the inmates (N=870) in the district jail of Mathura. Proforma related to general demographic information was filled by the examiner and the subjects were clinically examined using WHO 1997 "Oral Health Assessment Form RESULTS:This study revealed that 92.5% of the inmates were male. 53.8% never visited the dentist & 87% never received any type o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
4
4
1
Order By: Relevance
“…In the present study, the prevalence of dental caries was 53.1% which was higher than 44.5% according to National Oral Health Survey and Fluoride Mapping for general population. [15] The similar findings were reported by Sharma A et al [16] But the prevalence of current study was much lesser as compared to 64.9% which was reported by Rinki Hans et al, [9] 66% reported by Muni kumar et al, [10] 67.6% reported by Vittal Das Shetty et al, [5] 71.8% reported by Shailee Fotedar et al, [2] 78.7% reported by Dhankar K and Ingle et al [6] & Anup N et al, [17] 92.5% by Veera Reddy et al [18] and 98% reported by Nobile Carmelo et al [12] The high prevalence of dental caries might be due to increased number of untreated dental caries in prisoners when compared to the general population.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In the present study, the prevalence of dental caries was 53.1% which was higher than 44.5% according to National Oral Health Survey and Fluoride Mapping for general population. [15] The similar findings were reported by Sharma A et al [16] But the prevalence of current study was much lesser as compared to 64.9% which was reported by Rinki Hans et al, [9] 66% reported by Muni kumar et al, [10] 67.6% reported by Vittal Das Shetty et al, [5] 71.8% reported by Shailee Fotedar et al, [2] 78.7% reported by Dhankar K and Ingle et al [6] & Anup N et al, [17] 92.5% by Veera Reddy et al [18] and 98% reported by Nobile Carmelo et al [12] The high prevalence of dental caries might be due to increased number of untreated dental caries in prisoners when compared to the general population.…”
Section: Discussionsupporting
confidence: 79%
“…[4] Prisoners are psychologically, socially, morally and economically affected group, which makes them to neglect their oral health. [5][6][7] Plan of providing dental health services in prison, stood as a challenging part as the dental instruments used while screening and treatment are sharp in nature, which makes difficult task for jail authorities to provide safety of dentist against prisoners. [8][9][10] Oral health-related quality of life (OHRQoL) is as an individual's assessment of how the functional factors, psychological factors, social factors, and experience of pain/discomfort in relation to orofacial concerns affects his or her well-being.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the studies depicted that majority of the prisoners have poor oral health, for instance, one of the studies conducted in the District Jail of Mathura reported that 79% of the prisoners had a poor periodontal condition and dental caries, followed by 59.8% inmates had pro-mucosal lesions. However, this study also reported that all the inmates demonstrated signs of dental fluorosis; 58.6% had mild, 27.8% had moderate, and 4.3% had severe fluorosis [ 15 ]. On the contrary, another study conducted in the Central Jail of Gulbarga city reported that only 7.33% of inmates had dental caries among all the prisoners [ 1 ].…”
Section: Resultsmentioning
confidence: 99%
“… Forest plot of pooled magnitude of NCDs among prisoners of India [ 1 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. …”
Section: Figurementioning
confidence: 99%